PENGARUH MODEL PEMBELAJARAN INQUIRY TERBIMBING BERBASIS GAME EDUCAPLAY TERHADAP CRITICAL THINKING DAN HASIL BELAJAR GEOGRAFI KELAS X SMA N 3 BUKITTINGGI - Widya Shakira; Mentari Dian Pertiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of applying the Guided Inquiry model assisted by Educaplay Game on hydrological material to improve Critical Thinking and Learning Outcomes of SMAN 3 Bukittinggi students. This type of research is experimental research using purposive sampling technique. The samples in this study were X E4 class students as the experimental class who were given treatment using the Guided Inquiry model assisted by Educaplay Game and X E1 students as the control class. Data collection using pre-test and post-test instruments in the form of multiple choice and essay that has been tested for validity and reliability. The result of this study is that there is an effect of Guided Inquiry on hydrosphere material on Critical Thinking. Independent Sample t-Test analysis used to measure Critical Thinking where the significance value (Sig. 2-tailed) of 0.000 is smaller than 0.05 therefore Ho is rejected and Ha is accepted. For learning outcomes, the average post-test acquisition of the experimental class was 85.2 and the control class was 82. Data analysis using the Paired T-Test test from the calculated data obtained a significance level of 0.001 which is smaller than 0.05 indicates that Ho is rejected and Ha is accepted.